Managing Secrecy and Disclosure of Domestic Violence in Affluent Communities. Issue 2 (12th August 2016) - Haselschwerdt, Megan L.; Hardesty, Jennifer L.
Abstract: Although it is widely acknowledged that domestic violence (DV) can happen to anyone, there is scant research on affluent women's DV experiences. Using grounded theory, the present study examined how affluent mothers managed secrecy and disclosure of DV in the context of their community. Data consisted of interviews with 10 mothers and 17 service providers from one affluent community. The process of managing secrecy and disclosure of DV was nonlinear, ongoing, and strongly influenced by community culture and familial status. Mothers' secrecy and disclosure decisions (i.e., how and when mothers disclosed) and experiences (i.e., the type of responses they received upon disclosure) varied depending on whether they bought in or opted out of the culture of affluence during marriage. The resulting grounded theory has implications for future research on DV in affluent families and the broader literature on secrecy and DV disclosure.